Sedentary life in the context of educational attainment - Martinek, Lukáš; Tóthová, Valérie; Zeman, Marek (Jihočeská univerzita v Českých Budějovicích, Zdravotně sociální fakulta, 2015)
The article deals with the issue of sitting and sedentary lifestyles as a social problem of the healthy adult population of the Czech Republic in relation to the education achieved. The research sample consisted of 1,122 respondents, 544 men (48.5%) and 578 women (51.5%). The data were collected using a standardized questionnaire, IPAQ, which mapped physical activity in the last week. More than 41.3% of the respondents sit for more than 6 hours in a work week. Similarly, on weekends 39.4% of the respondents sit for more than six hours. People with a basic education spend the most time sitting on weekdays. 78% of respondents with a basic education spend four hours or more sitting on weekdays. Surprisingly, those with a university education show the largest decline in the hours spent sitting at the weekends (compared to weekdays). Prolonged sitting and sedentary lifestyle is a threat people should be warned about, because it is responsible for a series of pathologies of the human musculoskeletal system and predisposes excessive weight and obesity. The comparison of our results with similar studies points to a problem not only in the Czech Republic, but also in other economically developed societies. It is necessary to apply the knowledge of a sedentary lifestyle in primary prevention and carry it consistently into practice.
Sedavý způsob života v kontextu dosaženého vzdělání
Keywords: sedentary lifestyle; physical inactivity; time spent sitting; primary prevention; healthy adult population; sedavý způsob života; pohybová inaktivita; doba strávená sezením; primární prevence; zdravá dospělá populace